(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Harold Pinter, a playwright whose originality was so compelling that it has brought into thelexicon the term Pinteresque, to describe an atmosphere of expectation, where real characters speakunrealistically, or inconsequentially, as people actually do in everyday life. He evoked that atmosphereof dread simply by having his stage protagonists engage in conversational repetitiveness and seemingirrationally, served up as objects of interest in and by them. This paper shows the art of game and roleplaying that Pinter to explain the true appearance of human existence and situation. These conceptsemphasize the fear lurking just around the corner, the sense of menace that is prevalent due to animpending threat.